2011
DOI: 10.1182/blood-2010-01-266833
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cxcl12/Sdf-1 in adult mice decreases the quiescent state of hematopoietic stem/progenitor cells and alters the pattern of hematopoietic regeneration after myelosuppression

Abstract: The C-X-C-type chemokine Cxcl12, also known as stromal cell-derived factor-1, plays a critical role in hematopoiesis during fetal development. However, the functional requirement of Cxcl12 in the adult hematopoietic stem/progenitor cell (HSPC) regulation was still unclear. In this report, we developed a murine Cxcl12 conditional deletion model in which the target gene can be deleted at the adult stage. We found that loss of stroma-secreted Cxcl12 in the adult led to expansion of the HSPC population as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
201
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(220 citation statements)
references
References 39 publications
13
201
2
4
Order By: Relevance
“…FGF2 also slightly increased the mRNA levels of other genes expressed in OBs, including N-cad and Scf, in ELBOSs. These results were similar to those from a previous report, where the loss of Sdf-1 in the BM stroma of adult mice induced a decrease of Jag-1 and an increase of N-cad [48]. The secretion level of FGF2-induced SDF-1 in the ELBOS culture medium was decreased; this was not the case in the C166 culture medium.…”
Section: Cxcl5 In Stem Cell Nichesupporting
confidence: 81%
“…FGF2 also slightly increased the mRNA levels of other genes expressed in OBs, including N-cad and Scf, in ELBOSs. These results were similar to those from a previous report, where the loss of Sdf-1 in the BM stroma of adult mice induced a decrease of Jag-1 and an increase of N-cad [48]. The secretion level of FGF2-induced SDF-1 in the ELBOS culture medium was decreased; this was not the case in the C166 culture medium.…”
Section: Cxcl5 In Stem Cell Nichesupporting
confidence: 81%
“…It is well known that HSCs are retained in the marrow environment via the SDF1α/CXCR4 axis 40 and the use of pharmacological agents to disrupt this interaction leads to their egress from the marrow. 23 The high expression of SDF1α by the 3D-MSCs at both the RNA and protein levels indicated that perhaps they retain a high number of HSCs via forming a chemokine-rich environment.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that ongoing steadystate hematopoiesis requires strict retention of HSPCs in their BM niches, and that the loss of retention is thus associated with defects in hematopoiesis. There are few mechanisms, such as inducible genetic deletions of CXCR4 (19,55), CXCL12 (20), RAC1, and CDC42 GTPases (56,57), that result in increased numbers of HSPCs in the circulation and reduced repopulation potential. On the other hand, we demonstrate that FGF-2 or IGF-1 administration expanded HSPC numbers in the BM (data not shown and refs.…”
Section: Scf Enhances Hspc Migration Via Gsk3βmentioning
confidence: 99%
“…In addition to proliferation, GSK3β has been shown to be involved in the motility of various cells, including microglia, epidermal stem cells, human mast cells, and breast cancer cells (12)(13)(14)(15)(16), but its effect on the motility of immature hematopoietic cells has not been addressed. On the other hand, the chemokine CXCL12 (also termed stromal-derived factor-1, referred to herein as SDF-1) and its major receptor CXCR4 have well-characterized roles in directional motility and quiescence of human and murine HSPCs (17)(18)(19)(20). Of note, the migratory potential of human CD34 + HSPCs toward a gradient of CXCL12 in vitro correlates with the hematopoietic recovery following clinical autologous transplantations (21).…”
Section: Introductionmentioning
confidence: 99%